Propuesta de un empaque a base de Fibra de Estopa de Coco para la Empresa Palma Coco en Villavicencio- Meta (2021)
He objective of this research is to propose a biodegradable packaging based on coconut tow fiber with a glass container of an oil product for the Palma de Coco company in the city of Villavicencio. The current problem of the Palma Coco company is that it presents reports of breakdowns in the different processes of storage, transfers and exhibition of the samples of the coconut oil product, which is packaged in glass containers, a fragile material highly threatened by fractures, cracks, cracks and breakdowns in general, for which there is a primary need to reduce the amount of damage and economic losses without damaging the presence, presentation and commercial aspect of the product or the economic part of the company. The purpose of this work is to propose a protective packaging model based on coconut tow fiber as part of the coconut oil packaging aspect for the Palma Coco company, supported by an analysis of the regulatory framework related to the packaging system of products in Colombia.